2012
DOI: 10.1007/s12011-012-9323-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Zinc Supplementation Improves Spatial Memory in Rat Pups

Abstract: A large body of evidence supports an opinion that adequate dietary zinc is essential for prenatal and postnatal brain development. Behavioural effects of maternal supplementation with ZnSO 4 were analysed in rat pups with the Morris water task performance, a hole board and a T-maze. Wistar females during pregnancy and lactation received a drinking water solution of ZnSO 4 at doses of 16 mg/kg (group Zn16) or 32 mg/kg (group Zn32). Behavioural tests were conducted on the 4-week-old male rat pups. Zinc concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 37 publications
(48 reference statements)
4
14
0
Order By: Relevance
“…Flinn JM et al reported in a series of publications that enhanced zinc (10 ppm) consumption causes memory deficits in rats [19], [32] and potentiates memory impairment in transgenic disease mouse models [33], [34], while others observed improved performance of the animals in spatial memory tasks [35], [36]. In our experiments, we also observed improved performance of mice in contextual discrimination task.…”
Section: Discussionsupporting
confidence: 73%
“…Flinn JM et al reported in a series of publications that enhanced zinc (10 ppm) consumption causes memory deficits in rats [19], [32] and potentiates memory impairment in transgenic disease mouse models [33], [34], while others observed improved performance of the animals in spatial memory tasks [35], [36]. In our experiments, we also observed improved performance of mice in contextual discrimination task.…”
Section: Discussionsupporting
confidence: 73%
“…First, the effect of zinc supplementation on learning and memory impairments is dose dependent. Generally, zinc supplementation in a low dosage seems to improve the performance of animals in spatial memory tasks (Piechal et al, 2012) or the contextual discrimination task (Yang et al, 2013). However, memory deficits in rats after low dose of zinc supplementation were also observed (Flinn et al, 2005; Railey et al, 2010).…”
Section: The Role Of Zinc In Modulating Synaptic Functionmentioning
confidence: 99%
“…It should be noted that these deficits persisted into adulthood long after zinc nutriture had been reestablished [12]. More recently, rat pups born of dams receiving pre- and postnatal zinc supplementation showed significant improvements in memory as well as an increase in serum zinc levels compared to controls, indicating that zinc supplementation positively impacts early cognitive development [13]. Furthermore, there is some evidence to suggest that rats fed a zinc-supplemented diet after birth may be more resistant to subsequent diet-induced zinc deficiency [14].…”
Section: Zinc In Development and Neurogenesismentioning
confidence: 99%